一种供应链责任主体身份认证方法及系统 (2023)
本发明实施例提供一种供应链责任主体身份认证方法及系统，包括：根据责任主体的身份标识和用户密码生成责任主体的公-私密钥对，公-私密钥对包括系统主私钥和系统主公钥；根据系统主私钥和用户标识生成签名私钥；利用签名私钥对责任主体的用户数据进行数字签名加密，获取签名数据；利用身份标识对签名数据进行验证。本发明实施例提供的供应链责任主体身份认证方法及系统，在产生系统主私钥和签名私钥时加入了用户设定的密码，在使用签名时需要由用户标识、用户密码双重验证后进行签名，提升了主私钥和签名私钥的安全性，能有效防止验证不准确或者用户资料泄漏的问题发生。 The embodiment of the invention provides a supply chain responsibility subject identity authentication method and system, and the method comprises the steps: generating a public-private key pair of aresponsibility subject according to the identity of the responsibility subject and a user password, and enabling the public-private key pair to comprise a system main private key and a system main public key; generating a signature private key according to the system main private key and the user identifier; performing digital signature encryption on the user data of the responsibility subject byusing the signature private key to obtain signature data; and verifying the signature data by utilizing the identity identifier. According to the supply chain